2003
DOI: 10.1097/00006676-200305000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Kappa B Expression in Peripheral Blood Mononuclear Cells of Patients with Acute Pancreatitis

Abstract: An alteration of the characteristics of PBMCs occurs in the early phase of acute pancreatitis and may predispose patients to a higher risk of serious systemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Only two reports have investigated NF-ĸB activation in human acute pancreatitis. Satoh et al [17] found significantly higher levels of NF-ĸB activation in PBMNCs at admission, similar to our study. On the other hand, O’Reilly et al [34] recently detected significantly increased NF-ĸB activation in PBMNCs of acute pancreatitis patients within 24 h of symptom onset.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Only two reports have investigated NF-ĸB activation in human acute pancreatitis. Satoh et al [17] found significantly higher levels of NF-ĸB activation in PBMNCs at admission, similar to our study. On the other hand, O’Reilly et al [34] recently detected significantly increased NF-ĸB activation in PBMNCs of acute pancreatitis patients within 24 h of symptom onset.…”
Section: Discussionsupporting
confidence: 92%
“…PBMNCs were isolated from blood using a modification of the method described by Satoh et al [17]. Commercial kit (Chemicon’s Transcription Factor Assay Kit Cat No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, apelin-induced reductions of pancreatic ECM protein levels were associated temporally with apelininduced reductions in pancreatic NF-B activation, implying that apelin's induced reductions in pancreatic ECM levels are linked to its inhibition of NF-B activation. Interestingly, evidence of NF-B involvement in human AP has been reported (40).…”
Section: G146 Apelin and Pancreatitismentioning
confidence: 99%
“…Although the exact pathogenesis remains unclear [4] . Studies in recent years have found that NF-κB (nuclear factor kappa-B) which is a main factor in the genetic transcription of inflammation, presents high expression state in acute pancreatitis and plays an important role in the onset and turnover of acute pancreatitis together with other inflammatory cytokines [5][6][7] . Dexamethasone is the antagonist of a nonspecific inflammatory mediator [8] .…”
Section: Introductionmentioning
confidence: 99%